Research on the impact mechanism of user satisfaction with Software as a Service - Li, Shuwen (MATEC web of conferences, 2018)
Software as a Service(SaaS)has become a mainstream way for enterprises and governments to promote informatization. However, it is very easy for users to change their SaaS supplier due to low implementation costs. Improving user satisfaction with SaaS products and ensuring their continued usage by users present practical challenges that SaaS suppliers cannot ignore. The traditional information system success model only pays attention to the quality of products which is known as internal quality. This paper combines the internal quality features of SaaS with the suppliers’ quality and environmental quality. These two qualities constitute external quality, which also affect user satisfaction. The study comprehensively explores the impact mechanism of SaaS user satisfaction based on the integrated perspective of internal quality and external quality. We use SPSS23.0 and SmartPLS to examine the hypothesis with data from 212 valid questionnaires. The study finds that system, information, service, supplier, and environmental quality have a significant effect on user satisfaction, and the influence of service quality is the greatest.